STUDY OF THE EFFECT OF ETHANOL ALCOHOLS ON YEASTS AND FUNGI ISOLATED FROM THE NAIL - Jumana Sadiq Hassan; Maryam Issa Hameed; Ahmed Ail Hassen; Batool Saleh Chuaied; Zainab Ahmed Sabir; Mona Riyad Kamel (PT. Antis International Publisher, 2024)
The right to use alcoholic materials excessively, such as 75% ethanol concentration, which is produced locally by several companies, and the use of these materials as sterilizing agents to get rid of certain kinds of viruses or microorganisms, as happened recently due to the Corona virus outbreak, have resulted in an increase in resistance. This study, which involved bleaching a number of yeast species, including Candida albicans, Candida glabrata, Candida krusei, Candida tropicalis, Rhodotorula, and Aspergillus flavus, revealed the emergence of high resistance by those yeasts and fungi to the alcohols used EtOH, surgical, joonandjood, which was caused by certain types of microorganisms, including fungi and yeasts, and the emergence of resistant strains, particularly those that accompanied skin infections or nail injuries. This might be the result of patients' overuse of alcohol and the resistant strains that followed it